Microencapsulation via Spray-Drying of Geraniol-Loaded Emulsions Stabilized by Marine Exopolysaccharide for Enhanced Antimicrobial Activity - Ichrak Joulak; Samia Azabou; Emilie Dumas; Filomena Freitas; Hamadi Attia; Adem Gharsallaoui (Life, 2023)
The current study investigates the formation of microencapsulated geraniol powder, with the exopolysaccharide EPS-K1B3 produced by Halomonas caseinilytica K1, as wall material, using spray-drying. Evaluation of the antimicrobial activity of the functional emulsions, prepared at either pH 5 or pH 7, was carried out against Gram-positive (Listeria innocua (ATCC 33090)) and Gram-negative (Escherichia coli (DSM682)) bacterial strains. Results showed prolonged antimicrobial efficacy until 30 days of incubation for geraniol microcapsules compared to wet geraniol emulsions, which could confirm the ability of the spray-drying process to protect encapsulated geraniol for a longer period. The highest antimicrobial efficacy of geraniol microcapsules was observed against L. innocua at pH 5. Therefore, the influence of pH on the functional property of geraniol microcapsules could be highlighted beside the targeted bacterial strain.